Interventions in CHD Patients with Combined Left Main Stenosis and Chronic Coronary Artery Occlusion - Furkalo, Sergii M. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Combined left main coronary artery (LMCA) lesion and chronic coronary artery occlusion (CTO) significantly worsens the clinical course of patients with CHD, affecting the prognosis and complicating interventional treatment of this category of patients. Aim. To analyze the effectiveness and technical features of interventional procedures in patients with ischemic heart disease and left coronary artery lesion combined with CTO of one of the coronary arteries. Materials and methods. We included 30 patients with combined LMCA stenotic lesion and CTO of one of the main coronary arteries in the study. The average age of the patients was 62.4±9.7 years, 90% were men. Clinical manifestations were characterized by anginal syndrome of varying severity: 25 (83.3%) patients had CCS III, 23.3% of patients had diabetes mellitus, 19 (63.3%) patients had a history of MI in the area of the occluded artery, and the ejection fraction (EF) was 52.8±11.3%. Results. The lesion of the LCA was combined with the RCA CTO in 9 cases (30%). Occlusion of the CX and stenosis of the LM were recorded in 10 cases (33%). In 11 cases, combined lesion of the LCA and the LAD was recorded (37%). The technical success of CTO recanalization in the group was 86.6%. In 17 cases, stenting of the LM was performed before CTO intervention and stenting of the LM after CTO intervention in 10 cases. CTO recanalization without stenting of the LM was performed in 3 cases. The intervention beam time was 42.4±22.3 min, and the air rudder index was 1887.1±948.4 mGy. The main technique of CTO recanalization used in our series of patients was the AWE (antegrade wire escalation) technique. Retrograde access was used in 3 (10%) cases. No operative mortality was recorded. In one case, coronary artery perforation occurred. Conclusions. In patients with combined lesions of the LCA and CTO, where CABG is of high risk or not feasible, interventional approach can be successfully used. The priority of performing the intervention on the LCA or CTO depends on the anatomy of the coronary artery lesions and clinical manifestations of the disease.